DIAVOLUL ȘI ÎNGERII ÎN ROMANELE LUI ANDREI CODRESCU / THE DEVIL AND THE ANGELS IN ANDREI CODRESCU’S NOVELS - Cristina Matilda Vănoagă (Incursiuni în imaginar)
The paper discusses how Andrei Codrescu creates images of the Devil and angels in his novels. Partially, he explains in his essays the inspiration for building the postmodern representation in his novel. Inspired by reality, Codrescu disguises characters and events in imaginary constructions of a sacred manifesting mainly in the American landscape. The underground becomes a place of sacredness as perceived by a sexually permissive society. At the same time, the angels appear incapable of understanding the posthuman world or are revolted against their mission on earth. Another category of angels is represented by transferring the name to women enslaved by a false diabolical and sexually corrupted Devil.